The emergence of constitutions in the perspective of the Algerian experience - Lamzari, Moufida (Milev Journal of Research and Studies, 2017)
The constitutional law is a science that focuses on setting legal rules that regulate the State’s authority and organizes lives of the people who live on its soil in a way that guarantee respect and protection for both. The constitution is the logical result of the circumstances that surround it, regarding both its creation and content. Algeria as many others countries, issued a range of constitutions during its history within certain circumstances, in fact the first one was issued in September 1960 and it lasted only 23 days as the President at that time applied the section no. 59 including exceptional circumstances. Then came the Constitution of November 22, 1976 which adopted socialism as ideology, but it did not succeed in achieving the goals it was meant to consequently it was repealed by the constitution of February 29, 1989 that abandoned the socialist ideology and adopted liberalism that was applied in Law, Politics and Economy. AS this last Constitution was incomplete, the legislator modified it in 1996, then many other modifications have been succeeding until now.